Comparative Pharmacokinetics of Mitragynine after Oral Administration of Mitragyna speciosa (Kratom) Leaf Extracts in Rats - Avery, Bonnie A.; Boddu, Sai P.; Sharma, Abhisheak; Furr, Edward B.; Leon, Francisco; Cutler, Stephen J.; McCurdy, Christopher R. (Planta Medica, 2019)
Kratom (Mitragyna speciosa) has been examined for its opioid activity, especially for the treatment of opioid withdrawal and pain. Mitragynine, the most abundant alkaloid in kratom, is thought to be the major psychoactive alkaloid. An HPLC method was developed for the quantification of mitragynine in kratom leaf extracts. In addition, a multiple reaction mode based UPLC-MS/MS method was developed and validated for the quantification of mitragynine in rat plasma. Pharmacokinetic studies were performed by comparing a single intravenous dose of mitragynine (5 mg/kg, mitragynine hydrochloride) to a single oral dose of mitragynine (20 mg/kg, mitragynine hydrochloride), lyophilized kratom tea, and the organic fraction of the lyophilized kratom tea at an equivalent mitragynine dose of 20 mg/kg in rats. After intravenous administration, mitragynine exhibited a biexponential decrease in the concentration-time profile, indicating the fast distribution of mitragynine from the systemic circulation or central compartment to the peripheral compartments. Mitragynine hydrochloride, lyophilized kratom tea, and the lyophilized kratom tea organic fraction were dosed orally and the absolute oral bioavailability of mitragynine in rats was found to be 1.5- and 1.8-fold higher than that of mitragynine dosed alone. The results provide evidence that an equivalent oral dose of the traditional preparation (lyophilized kratom tea) and formulated/manufactured products (organic fraction) of kratom leaves provide better systemic exposure of mitragynine than that of mitragynine dosed alone.
Keywords: Mitragyna speciose; Rubiaceae; kratom; mitragynine; bioavailability; pharmacokinetics